Analisis Konsep Ketenangan Immanuel Kant - Wafa Khanza Arfani (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze Immanuel Kant's concept of sobriety. This research uses a qualitative approach by applying a descriptive-analytical method. The formal object of this study is Immanuel Kant's views, while the material object is serenity. The results and discussion of this study indicate that Immanuel Kant's view of sobriety can be conceptualized into two, first, moral courage, that is, someone who has moral composure is able to act in accordance with moral obligations, second, the establishment of sobriety, that is, someone who achieves moral equanimity will have inner peace that radiates of their attitudes and actions. This study concludes that calm according to Kant is not seeking emotional satisfaction or personal pleasure, but involves balance and stability in acting according to universal and rational moral principles.